TRANSFORMASI HADIS DARI SUMBER NORMATIF KE KERANGKA PENDIDIKAN ISLAM KONTEMPORER - Maya Agisty Maya (Yayasan Baitul Hikmah al-Zain, 2026)
This study examines the integration of hadith as the epistemological foundation of Islamic education through the perspective of Surah Al-Fatihah, which is considered the core of the teachings of the Qur'an and the spiritual foundation for character building. It focuses on the Prophet's hadiths about the greatness of Surah Al-Fatihah as an epistemological and pedagogical basis for formulating comprehensive Islamic educational goals and objectives. The research method is a literature study, examining classical-contemporary interpretations, authentic hadiths, and Islamic education literature. Content analysis finds that Surah Al-Fatihah contains structured values of monotheism, worship, morality, and social values. Combined with the Prophet's prophetic methods such as positive motivation, humanistic approaches, and stimulation of curiosity, this forms an integrative and transformative educational framework. Hadith on the virtues of studying the Qur'an emphasizes that the object of education is not only cognitive, but also attitude and behavior. Conclusion: The integration of Surah Al-Fatihah and related hadith produces a holistic Islamic education paradigm, balanced between spirituality, intellect, and morals, forming students who are strong in faith, noble in character, and adaptive to modern life.